DETERMINAN PROFITABILITAS: KAJIAN PENGELOLAAN FAKTOR INTERNAL DAN EKSTERNAL PERUSAHAAN TEKSTIL DAN PRODUK TEKSTIL (TPT) YANG TERDAFTAR DI BURSA EFEK INDONESIA - Nugraheni Siwi (Universitas Pakuan, 2019)
This research looks at the effect of internal factors or microeconomics and external factors or macroeconomic factors on profitability of textiles and textiles products companies. The result showed that partially, only current ratio and the interest rates which have significant impact on ROA. simultanously, internal and external factors have significant impact on ROA. Managerial implication based on this research are, the companies should apply liquidity risk management like mitigation on liquidity crisis and liquidity risk bearing analysis also look for another fund resources to decrease interest rates expenses.